Unusual microwave response and bulk conductivity of very thin FeSe₀.₃Te₀.₇ films as a function of temperature - Barannik, A.A.; Cherpak, N.T.; Yun Wu; Sheng Luo; Yusheng He; Kharchenko, M.S.; Porch, A. (Физика низких температур, 2014)
Results of X-band microwave surface impedance measurements of FeSe₁–xTex very thin film are reported. The effective surface resistance shows appearance of peak at T ≤ Tc when plotted as a function of temperature. The authors suggests that the most well-reasoned explanation can be based on the idea of the changing orientation of the microwave magnetic field at a S–N phase transition near the surface of a very thin film. The magnetic penetration depth exhibits a power-law behavior of L(T) CTn, with an exponent n ≈ 2.4 at low temperatures, which is noticeably higher than in the published results on FeSe₁–xTex single crystal. However the temperature dependence of the superfluid conductivity remains very different from the behavior described by the BCS theory. Experimental results are fitted very well by a two-gap model with Δ₁/kTc = 0.43 and Δ₂/kTc = 1.22, thus supporting s±-wave symmetry. The rapid increase of the quasiparticle scattering time is obtained from the microwave impedance measurements.